2022
DOI: 10.3389/fmicb.2022.858192
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bacterium, Butyricimonas virosa, Preventing HFD-Induced Diabetes and Metabolic Disorders in Mice via GLP-1 Receptor

Abstract: Knowledge of the impact of the gut microbiota on human health has increased, and modulation of the bacterial community is now considered a therapeutic target for various diseases. Certain novel bacterial species have probiotic properties associated with improvement in obesity and related metabolic disorders. The relative abundance of Butyricimonas spp. is correlated with metabolic parameters; however, the physiological role of Butyricimonas in metabolic improvement is unclear. In this study, live and heat-kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 43 publications
(47 reference statements)
0
17
1
Order By: Relevance
“…Interestingly, although a positive correlation with BPH indicators was confirmed, Butyricimonas abundance was further increased by finasteride treatment. Despite recent reports on the positive effects of Butyricimonas [ 33 ], the abundance of Butyricimonas was consistently positively correlated with BPH markers in our study. Therefore, further studies are required.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, although a positive correlation with BPH indicators was confirmed, Butyricimonas abundance was further increased by finasteride treatment. Despite recent reports on the positive effects of Butyricimonas [ 33 ], the abundance of Butyricimonas was consistently positively correlated with BPH markers in our study. Therefore, further studies are required.…”
Section: Discussioncontrasting
confidence: 99%
“…They have been reported to aggravate metabolic disorders in diabetic patients in relation to their energy metabolism and insulin sensitivity [ 32 ]. Butyricimonas has been reported to improve hyperglycemia through the regulation of GLP-1R in mice fed a high-fat diet and to be associated with lipid metabolism [ 33 , 34 , 35 ]. The increased abundance of Anaerotruncus is directly related to an increase in inflammatory cytokines due to aging [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of metabolic disorders with metformin and statins has been shown to significantly increase the relative abundance of Butyricimonas in the gut, and this has been significantly associated with metabolic parameters [ 60 , 61 ]. Lee et al reported that Butyricimonas could prevent high fat diet-induced diabetes and metabolic disorders in mice via the GLP-1 receptor [ 62 ]. Butyricimonas has also been negatively correlated with insulin resistance and obesity in humans [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…This genus has been positively associated with the adoption of a high-fat diet [158], but also with normal BMIs in another study [159]. Moreover, the B. virosa species has previously been stated to have a beneficial effect on obesity and T2D by promoting SCFA production [160] and thus the secretion of the glucagon-like peptide-1 (GLP-1) [161], an incretin that activates glucose-dependent insulin secretion and inhibits glucagon release [162]. Conversely, Sutterella , which was more abundant in the group with poorer HEIs, has been reported to be positively correlated with the likeness of developing T2D [163].…”
Section: Discussionmentioning
confidence: 99%